2019
DOI: 10.3892/ijmm.2019.4169
|View full text |Cite
|
Sign up to set email alerts
|

Detection of N6‑methyladenosine modification residues (Review)

Abstract: Among a number of mRNA modifications, N 6 -methyladenosine (m 6 A) modification is the most common type in eukaryotes and nuclear-replicating viruses. m 6 A has a significant role in numerous cancer types, including leukemia, brain tumors, liver cancer, breast cancer and lung cancer. Although m 6 A methyltransferases are essential during RNA modifications, the biological functions of m 6 A and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 79 publications
(150 reference statements)
0
45
0
Order By: Relevance
“…The ultimate message we get from all these recent papers about epitranscriptomic modifications in glioma is that we are likely observing only the tip of the iceberg, and we will surely find many more sophisticated mechanisms which can finely modulate transcript fate in glioma cells. As the techniques employed to analyzeepitranscriptomic modifications become more and more refined [65,66], we become able to detect subtle changes even in little portions of the transcripts, as clearly shown in the case of the unique cytosine methylation event in 28S rRNA by NSUN5. As Janin's paper teaches, a single, tiny change in one nucleotide of a single type of RNA can dramatically change a cell's fate [55].…”
Section: Glioblastoma Stem Cells and U87 Glioblastoma Cell Linementioning
confidence: 92%
“…The ultimate message we get from all these recent papers about epitranscriptomic modifications in glioma is that we are likely observing only the tip of the iceberg, and we will surely find many more sophisticated mechanisms which can finely modulate transcript fate in glioma cells. As the techniques employed to analyzeepitranscriptomic modifications become more and more refined [65,66], we become able to detect subtle changes even in little portions of the transcripts, as clearly shown in the case of the unique cytosine methylation event in 28S rRNA by NSUN5. As Janin's paper teaches, a single, tiny change in one nucleotide of a single type of RNA can dramatically change a cell's fate [55].…”
Section: Glioblastoma Stem Cells and U87 Glioblastoma Cell Linementioning
confidence: 92%
“…Currently, a massive number of technologies have been developed for m 6 A detection based on the immunohistochemistry or hybridization properties ( Ovcharenko and Rentmeister, 2018 ). According to their detection performance, these technologies can be classified into the semiquantitative, quantitative, and precise location detection methods ( Zhu et al, 2019 ; Table 1 ).…”
Section: Advances In Technologies For M 6 a Detectmentioning
confidence: 99%
“…Among these, m6A modification is the most prevalent one in eukaryotes, which occurs in mammalian mRNAs, long noncoding RNAs, micro RNAs, involving in many RNA functions such as mRNA stability, splicing, transport, localization and translation, primary microRNA processing and RNA‐protein interactions . The levels of m6A modification in mRNAs were usually controlled by so‐called ‘reader’, ‘writer’ and ‘eraser’ . The ‘writer’, which is a high conserved methylase complex, containing methyltransferase like 3 (METTL3), methyltransferase like 14, Wilms’ tumour 1‐associating protein, RNA‐binding motif protein 15, Vir like m6A methyltransferase associated, Fl(2)d‐associated complex component and Hakai…”
Section: Introductionmentioning
confidence: 99%
“…15 The levels of m6A modification in mRNAs were usually controlled by so-called 'reader', 'writer' and 'eraser'. 16,17 The 'writer', which is a high conserved methylase complex, containing methyltransferase like 3 (METTL3), 18 methyltransferase like 14, 18 Wilms' tumour 1-associating protein, 19 RNA-binding motif protein 15,20,21 Vir like m6A methyltransferase associated, 18,22 Fl(2)d-associated complex component 20 and Hakai. 23 Recent studies showed that m6A modification played essential roles in tissue development, stem cell formation and differentiation, 24,25 control of heat shock response 26 and circadian clock controlling, 27 as well as in tumours formation.…”
Section: Introductionmentioning
confidence: 99%